Britain, Italy and the Origins of the Cold War - Pedaliu, E. author. aut Link
XI, 239 p.
Keywords: Effie G.H. Pedaliu analyzes the British Labour government's contribution to the postwar reconstruction of Italy. The book focuses on five areas: the punishment of war criminality; the reconstruction of the Italian armed forces; the Italian elections of April 1948 and Italy's institutional role in western security arrangements and on European integrative bodies. It reveals that British policy towards Italy was underpinned not only by power politics but also by moral and ideological considerations.